Cardiogenic shock in pregnancy: Analysis from the National Inpatient Sample - Jennifer Banayan; Sarosh Rana; Ariel Mueller; Avery Tung; Hadi Ramadan; Zoltan Arany; Junaid Nizamuddin; Victor Novack; Barbara Scavone; Samuel M. Brown; Sajid Shahul (Taylor & Francis Group, 2017)
Objective: Cardiogenic shock (CS) may occur during pregnancy and dramatically worsen peripartum outcomes. Methods: We analyzed the National Inpatient Sample from 2002 to 2013 to describe the incidence of, risk factors for and outcomes of CS during pregnancy. Results: Of the 53,794,192 hospitalizations analyzed, 2044 were complicated by CS. The mortality rate in peripartum women with CS was 18.81% versus 0.02% without. It occurs more often during postpartum (58.83%) as compared with delivery (23.47%) or antepartum (17.70%) hospitalizations. Factors associated with CS -related death included cardiac arrest, renal failure, and sepsis. Conclusions: CS during pregnancy occurs more commonly in the postpartum period and is associated with a high mortality.